Kinerja Aparatur Sipil Negara (ASN) dalam Pelayanan Pembuatan e-KTP di Zona VIII Kecamatan Sematang Borang - Ramadhan, Rama; Isabella, Isabella; Kencana, Novia (Universitas Indo Global Mandiri, 2024)
The ability of the State Civil Apparatus to provide services to the community is crucial in ensuring the smooth running of government administrative processes at the lowest level. Through this research, the researcher intends to find out how the State Civil Apparatus performs, especially in the process of providing e-KTP services to the community. This research itself is located in Zone VIII, Sematang Borang District, using qualitative methods and a case study approach. The results of this research show that the e-KTP making service in Sematang Borang District has not been running optimally, which is caused by various factors, including facilities or work tools that often have errors when they are used, which makes work a little hampered by the large number of people who want to make an e-KTP, the place can be said to be not very suitable because it is still shaped like a normal house, the parking space is narrow, and the human resources are minimal. The solution that the author can provide is that it is necessary to carry out evaluation and restructuring measures in terms of work facilities or tools in Zone VIII, Sematang Borang District, expanding the premises and also adding Human Resources, so that work is optimal and in accordance with applicable operational hours.